1993
DOI: 10.1182/blood.v82.12.3701.3701
|View full text |Cite
|
Sign up to set email alerts
|

Infection of peripheral blood mononuclear cells by hepatitis C virus in mixed cryoglobulinemia

Abstract: A striking association between hepatitis C virus (HCV) infection and mixed cryoglobulinemia (MC) has been shown; thus, HCV seems to play an important etiopathogenetic role in this lymphoproliferative disorder. Because HCV is both a hepatotropic and lymphotropic virus, this study aimed to investigate the prevalence of HCV infection of peripheral blood mononuclear cells (PBMCs) in a series of 16 patients with type II (IgMk) MC. Antibodies against HCV were detected by commercially available kits (Second Generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
11

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(108 citation statements)
references
References 0 publications
2
95
0
11
Order By: Relevance
“…Several studies from different patient populations [33,57] reported a strong association between mixed cryoglobulinaemia and HCV infection, varying from 80% to 90% of cases. Moreover, the presence of viral replication (negative-stranded viral RNA) in the peripheral lymphocytes, bone marrows and lymph nodes from mixed cryoglobulinaemia patients, with or without complicating NHL, reinforces the hypothesis of a possible causative role of HCV in this disorder [34,[36][37][38]42].…”
Section: Hcv and Cancer 713mentioning
confidence: 59%
See 2 more Smart Citations
“…Several studies from different patient populations [33,57] reported a strong association between mixed cryoglobulinaemia and HCV infection, varying from 80% to 90% of cases. Moreover, the presence of viral replication (negative-stranded viral RNA) in the peripheral lymphocytes, bone marrows and lymph nodes from mixed cryoglobulinaemia patients, with or without complicating NHL, reinforces the hypothesis of a possible causative role of HCV in this disorder [34,[36][37][38]42].…”
Section: Hcv and Cancer 713mentioning
confidence: 59%
“…Table 2 summarizes the main extrahepatic manifestations that can be associated with chronic HCV infection: they are immune-mediated and/or lymphoproliferative disorders. As HCV is both a hepato-and lymphotropic virus [36][37][38], it is likely that HCV infection of T-and B-lymphocytes could at least, in part, be responsible for these disorders often observed in chronically infected individuals. HCV, alone or in combination with other factors, i.e.…”
Section: Chronic Hcv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and serological studies have emphasized a possible etiological role of different viral infections [6][7][8], although the specificity of primary IgG is still unclear and understanding of the early, pathogenic steps is currently slight. Recently, the finding of antibodies to the hepatitis C virus (HCV) [9][10][11][12][13] and of HCV-RNA sequences in the sera [12][13][14][15] and in mononuclear cells [16,17] of a large proportion of patients with MC suggested that HCV may be relevant to the onset and/or development of this disorder. However, it is not clear whether the appearance of cryoglobulinaemia is related to antibodies directed against a defined antigenic region; similarly, comparative analysis of the response to specific HCV epitopes in HCV-infected patients with (MC ) and without (MC ÿ ) cryoglobulinaemia is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…A major pathogenetic role of hepatitis C virus (HCV) infection in the occurrence of mixed cryoglobulinaemia (MC) type II is now well documented (Ferri et al, 1993). Recently, anti-HCV antibodies and viral sequences have been observed in a substantial number of patients with non-Hodgkin's lymphoma not associated with cryoglobulinaemia, extending the spectrum of lymphoid disorders possibly related to HCV (Ferri et al, 1994).…”
mentioning
confidence: 99%